2016
DOI: 10.1002/qj.2752
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of tropical cyclone intensification rate on sea‐surface temperature

Abstract: The dependence of tropical cyclone intensification rate on the sea-surface temperature (SST) is examined in the prototype problem for tropical cyclone intensification on an fplane using a three-dimensional, non-hydrostatic numerical model. The effects of changing the SST are compared with those of changing the latitude examined in a recent article. It is found that the dependence of intensification rate on latitude is largest when the SST is marginal for tropical cyclone intensification (26 • C) and reduces in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…Taken together, the results of Črnivec et al () and the present study indicate that tropical cyclone intensification rate is sensitive to both the environmental sounding used and the SST.…”
Section: Implications For Tropical Cyclone Modellingsupporting
confidence: 86%
See 2 more Smart Citations
“…Taken together, the results of Črnivec et al () and the present study indicate that tropical cyclone intensification rate is sensitive to both the environmental sounding used and the SST.…”
Section: Implications For Tropical Cyclone Modellingsupporting
confidence: 86%
“…In a recent paper we showed that the intensification rate depends strongly on the SST (Črnivec et al , ) so that, for example, a 1° increase in SST when using the Willis Island sounding would be expected to significantly elevate the intensification rate. In that paper we showed that a larger SST leads to an increase in the surface moisture fluxes, which, in turn, result in higher values of near‐surface moisture, equivalent potential temperature and, most significantly, to a larger radial gradient of diabatic heating rate in the lower to mid troposphere.…”
Section: Implications For Tropical Cyclone Modellingmentioning
confidence: 98%
See 1 more Smart Citation
“…() and C̆rnivec et al . (), except that a larger inner grid‐mesh region with constant grid spacing is used here. Specifically, the outer domain is 1500 × 1500 km 2 in size, with variable spacing increasing to 10 km near the domain boundaries.…”
Section: The Numerical Modelmentioning
confidence: 99%
“…Of course, there have been numerous studies that discussed the interaction between the warm ocean and an overlying TC (e.g., Chan et al, 2001;Cione & Uhlhorn, 2003;Crnivec et al, 2016;Shay et al, 2000;Wu et al, 2007). Of course, there have been numerous studies that discussed the interaction between the warm ocean and an overlying TC (e.g., Chan et al, 2001;Cione & Uhlhorn, 2003;Crnivec et al, 2016;Shay et al, 2000;Wu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%